The Future of Work in Agriculture : Some Reflections - Christiaensen, Luc; Rutledge, Zachariah; Taylor, J. Edward (World Bank, Washington, DC, 2020)
As countries develop (and food saturation takes hold), agriculture's role as domestic employer declines. But the broader agri-food system also expands, and the scope for agriculture-related job creation shifts beyond the farm. Historically, technological revolutions have shaped and been shaped by these dynamics. Today, a digital revolution is taking hold, affecting agricultural labor and skill demands. In this process, societies evolve from having a surplus to a shortage of domestic farm labor, typically met largely by foreign agricultural wage workers. Yet, anti-immigration sentiments are flying high in migrant-destination countries, and robots in the fields and packing plants offer an alternative. Agricultural trade may be similarly challenged. In the world's poorest countries, particularly in Africa, labor productivity in agriculture remains at historically low levels. So, what can the role of agriculture as a source of employment be in the future? This viewpoint elaborates on these trends and reviews several policy options, including inclusive value chain development, better immigration policies, social insurance schemes, and ramp up in agricultural education and extension.